Maternal and child health services during COVID-19 in India: Highlighting the role of primary care physicians in maintaining continuum of care - Saurabh Sharma; Sumit Aggarwal; Kh. Jiten Kumar Singh; Lucky Singh; Asheber Gaym; Damodar Sahu; Tulsi Adhikari; Saritha Nair; Anil Kumar; Atul Juneja; Mendu Vishnu Vardhana Rao (Journal of Family Medicine and Primary Care)
Background: This study aims to address the lack of substantial evidence regarding the effect of COVID-19 on maternal and child health (MCH) services in India and also highlight the role of primary care physicians in maintaining essential services during a pandemic. While studies conducted worldwide and in India have examined the effects of COVID-19 on these services, a significant gap in robust evidence remains. Methods: Forty-two districts were selected randomly from seven regional states of India. Data on five selected MCH indicators were extracted from HMIS for the months from March to June 2019 and 2020. Relative changes in service utilization for each month from March to June over the two years were compared. Comparisons were also made between the selected districts based on the COVID-19 categorization into red and green zones. Results: COVID-19 and its associated restrictive measures created significant disruption to essential MCH service utilization in India across all states reviewed. Both institutional, and outreach services were impacted; however, hospital-based services were more impacted. Institutional deliveries and emergency obstetric services saw a decline in March and April 2020 which gradually improved between May and June in some states. Immunization sessions held in 2020 observed a decrease in April. Conclusions: The analysis indicates a disruption in service delivery during the initial phase of the lockdown. However, the services resumed gradually as national and state-specific operational guidelines were implemented to maintain a continuum of care.